William Montague Cobb: Near the African diasporic origins of activist and biocultural anthropology. Issue 4 (11th November 2021) - Blakey, Michael L.; Watkins, Rachel
Abstract: William Montague Cobb, AB, MD, PhD, was the first African American PhD in anatomy and physical anthropology. He produced 1, 100 publications while a professor at Howard University. His influence on the civil rights struggle from the 1930s to 1970s was profound as were his contributions to science and medical history. This article shows how he continued the activist and interdisciplinary traditions of African diasporic intellectuals and that these innovated what is today labeled biocultural anthropology, which focuses on the political, economic, and other societal influences on human biology and health. The human biology of the White "mainstream" has tended toward reductionism, biodeterminism, and eugenics. It drew a causal arrow from biology to society. Had they been able to listen to Black intellectuals, the world might have avoided the tragedy of mid‐20th century eugenics and its long continuing biodeterministic shadow.